2021
DOI: 10.1155/2021/2923700
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for Predicting Survival in Advanced Gastric Cancer after Neoadjuvant Chemotherapy and Radical Surgery

Abstract: Background. Neoadjuvant chemotherapy (NAC) with subsequent radical surgery has become a popular treatment modality for advanced gastric cancer (AGC) worldwide. However, the survival benefit is still controversial, and prognostic factors remain undetermined. Aim. To identify clinical parameters that are associated with the survival of AGC patients after NAC and radical surgery and to establish a nomogram integrating multiple factors to predict survival. Methods. We reviewed the medical profiles of 215 AGC patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Liu et al [ 4 ] suggested that a nomogram could be a promising clinical tool for assessing OS in patients with Siewert type II AEG after preoperative radiotherapy. Moreover, factors other than ypT and ypN stages significantly influence patient prognosis, therefore, they should be considered when establishing individual prediction models[ 31 - 34 ]. In this study, data were retrieved from a specific cancer database (SEER) to identify potential prognostic factors, specifically for patients with Siewert II AEG receiving NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 4 ] suggested that a nomogram could be a promising clinical tool for assessing OS in patients with Siewert type II AEG after preoperative radiotherapy. Moreover, factors other than ypT and ypN stages significantly influence patient prognosis, therefore, they should be considered when establishing individual prediction models[ 31 - 34 ]. In this study, data were retrieved from a specific cancer database (SEER) to identify potential prognostic factors, specifically for patients with Siewert II AEG receiving NAC.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, NAC was introduced into the integrated treatment modality for LAGC and soon became popular [3].…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy (NAC) with subsequent radical surgery has become a popular treatment modality for LAGC worldwide. However, the survival bene t is still controversial, and prognostic factors remain undetermined [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been some shortcomings. In a study published in 2021, the model was validated internally using the bootstrap method, lacking external validation in an independent cohort from a different institution [ 29 ]. Another study developed and validated a nomogram for GC patients using a multicenter database in Korea [ 30 ], however, it mainly focused on the clinical features and pathological results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the nomogram, which is a simple graphical visualization combining and quantifying all independent prognostic factors, plays an increasingly vital role in medical sciences and clinical studies [ 27 ]. Although there are some prognostic nomograms available for gastric cancer [ 28 , 29 , 30 ], only a few of them considered the patient’s inflammatory and nutritional factors, which are simple and effective risk factors. Therefore, in order to predict the prognosis of GC accurately, we incorporated the clinicopathologic features and preoperative inflammatory and nutritional factors to propose a nomogram and perform tests to validate whether this model could predict the prognosis more accurately compared with traditional TNM staging systems.…”
Section: Introductionmentioning
confidence: 99%